2001
DOI: 10.1002/dys.184
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the relationship between dyslexia and offending in young people and the implications for the training system

Abstract: A screening study was undertaken which involved 50 young offenders, serving sentences of various lengths, all from the largest young offenders' institution in Scotland. All 50 were screened for dyslexia and a number received a more detailed follow-up assessment. The results of the screening showed that 25 of the young offenders (50%) were dyslexic to some degree. This finding has implications for professionals, particularly in respect of follow-up assessment and support, and for politicians in relation to issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 5 publications
2
21
0
1
Order By: Relevance
“…Our findings are consistent with earlier studies regarding overlaps between reading problems and ADHD and depression, and extend the literature with several new findings; the excess risks of OCD, bipolar disorder, substance use disorder, and criminality have not been previously documented in samples with reading problems. The associations between reading problems and substance use disorder, and criminality, are however in keeping with prior small studies suggesting that reading problems are common in populations under drug treatment (Yates, 2013) forensic psychiatric care (Dåderman et al, 2004) and prison care (Kirk & Reid, 2001;Lindgren et al, 2002).…”
Section: Co-occurrence Analyses: Risks Of Psychiatric Disorders and Vsupporting
confidence: 59%
See 1 more Smart Citation
“…Our findings are consistent with earlier studies regarding overlaps between reading problems and ADHD and depression, and extend the literature with several new findings; the excess risks of OCD, bipolar disorder, substance use disorder, and criminality have not been previously documented in samples with reading problems. The associations between reading problems and substance use disorder, and criminality, are however in keeping with prior small studies suggesting that reading problems are common in populations under drug treatment (Yates, 2013) forensic psychiatric care (Dåderman et al, 2004) and prison care (Kirk & Reid, 2001;Lindgren et al, 2002).…”
Section: Co-occurrence Analyses: Risks Of Psychiatric Disorders and Vsupporting
confidence: 59%
“…Reading problems and psychiatric disorders 4 reading problems occur more often than would be expected by chance in forensic psychiatry (Dåderman et al, 2004) and correctional facilities (Kirk & Reid, 2001;Lindgren et al, 2002).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…A high percentage of individuals in UK and Swedish prisons with reading difficulties or dyslexia (30-52% of all prison inmates in tested prisons ) would suggest that many leave mainstream education unable to find gainful employment and are forced to use illegal means to support themselves and their families [46][47][48][49][50][51]. Some individuals with dyslexia (depending on educational and severity) may find it very difficult, if not impossible, to learn to read, write or do mathematics [52].…”
Section: Adults -Unsuccessful People With Dyslexiamentioning
confidence: 99%
“…The relationship between selfreported reading and spelling difficulties and their objective measured skills in reading and spelling has, however, been explored among incarcerated adults (Jones, Asbjørnsen, Manger, & Eikeland, 2010;Kirk & Reid, 2001). In a recent study of the prison population in Norway, it was revealed that self-reported difficulties shared little variance with their objective measured skills in reading and spelling.…”
Section: Introductionmentioning
confidence: 96%